(3EQTGO GdWGdHjf Edi fgL GdeSJQTOjfs - (3GdSjhQj, GdMdj, GdCSOj, GdebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826(3g`s ((3CMeO Hf eMeO GdMOGO GdYGedjs)
(3ChdgG (B:s
(3CMOgeG GJMOGH GdBNQ cGdghGA GdLGPH ddeGA HGdeU(B. (3CeG GdKGfj abGdhG EfeG jdRe eG PcQJg ef GdJOGNd(B...s
(3BNQgG (B:s
(3hgh EUWdGMG(B: (3EXgGQ GdEjeGf hEHWGf GdcaQ CYPGfG Gddg hEjGce ef GdcaQ hGdaSb hGdfaGb(B... (3hdfNJe cJGHfG gPG HOYGA TQja(B...s
(3JHUQI GdYfhGf (B:s
(3fgL GdeSJQTOjf(B: (3ddMSf Hf jhSa GdMdjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B282s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B470s
(3GdCYdGe(B: (3L(B7(3, U(B282s
Keywords: (3GdJhMjO hGdedd hGdfMds